Hobohemia and the crucifixion machine : rival images of a new world in 1930s Vancouver (2014)
In this short excerpt, written sometime between 1944 and 1947, Theodor Adorno registers the tragic effects of fifteen years of global depression and war with a horrifying revision of Walter Benjamin’s pre-war dream about the possibility of revolutionary change. The beggar, whose disappearance Benjamin had imagined as a sign of the disappearance of all classes, becomes in Adorno’s wilful misreading a much more complicated figure. In Adorno’s rendering, because the beggar is the target of the violence that must first be done so that myth can achieve the desired result, sleep comes to the child only by first remembering and then forgetting the hurts inflicted upon the homeless man in the shadows. This process is made all the easier by articulat- ing the man’s poverty with the appearances of racial inferiority.2 Effectively effaced and made an abstract figure, yet still all too human in his ability to experience pain, Adorno’s beggar is necessary to the functioning of the whole, not because he can work but because he can suffer, allowing the rest of us to remember, and then forget, and then sleep. Adorno manages to find a kernel of utopian content in this nursery rhyme by proposing that the bourgeois dream of physically expelling each and every beggar from the whole would, in reality, “make good everything that was ever done to him and can never be made good.”3 In his mind, justice for each individual historical act of persecution is an impossible goal since the very act of calculating an equivalent punishment would make one “the mouthpiece, against a bad world, of one even worse.”4 Nonetheless, Adorno still imagines that the beggar could inflict severe damage by accepting his removal from “civilization,” thereby allowing its citizens to stamp out within themselves the only remaining “portion of nature” yet to succumb to rationalization. In this logic, it is only outside of this society — now left alone with its dialectic of enlightenment, where Hitler or Hollywood represented the only choice that remained — that the abject beggar finally “glimpses peace without the wretchedness of others”: “Have now peaceful mind, beggar home shall find.” Regrettably, in our present context, Adorno’s final question — “Would not the beggar, driven out of the gate of civilization, find refuge in his home- land, freed from exile on earth?” — originates in a kind of curiosity about the possibilities of a utopia that most Canadian historians have learned to leave behind, an occasional object of, but not a guide to, critical historical practice. I offer in this book’s opening chapters an excursus into the beggar’s “homeland,” doing so as something of an antidote to this contemporary his- toriographic departure away from utopia’s long-standing attractions.